Collective impacts of LPGOD plasma and plasma activated water treatment in rice (Oryza sativa L.): Plasma activated water treatment in rice - Rashid, Mamunur; Alam, MS; Talukder, Mamunur Rashid (SAARC Journal of Agriculture, 2022)
Combined effects of plasma seed treatment and plasma activated waters (PAW) application on paddy was explored. Low pressure (100 torr) glow oxygen discharge (LPGOD) plasma was used for seed treatment and germination test revealed that 90s seed treatment duration produced highest seed germination of ~96% which is the highest paddy seed germination rate obtained through plasma technology. Plasma activated water (PAW) was prepared with submerged atmospheric pressure air discharge plasma jet. PAW was sprayed 1-5 times to the paddy plants. Field study was divulged that: (a) seed germination percentage was increased by ~10.76% with respect to control; (b) plants growth parameters were enhanced because of combined consequences of plasma seed treatment along with PAW application; (c) defense mechanisms of plants were improved, (d) concentrations of total soluble protein and sugar were increased in the paddy grains, and (d) yield was enhanced by ~16.77%. SAARC J. Agric., 20(2): 17-30 (2022)